The significance of tumor-associated immune response in molecular taxonomy, prognosis and therapy of colorectal cancer patients - Nearchou, Andreas; Pentheroudakis, George (Annals of Translational Medicine, 2016)
The importance of host immune response in colorectal cancer (CRC) has been constantly revealed through the last 10 years. A number of relevant immune markers have been introduced as prognostic and are now been used alone or in combination with each other in clinical practice. Efforts establishing a worldwide consensus on the implications of immune-profiles in conjunction to other factors are designed in the right direction in order to more effectively categorize patients with CRC in groups that might benefit from currently used or future applied therapies. On the other hand, a number of clinical trials have evolved the application of immunotherapies in patients with CRC both in the adjuvant and palliative setting.